Tyrosine kinase inhibitors: potential use and safety considerations in HIV-1 infection. Issue 5 (4th May 2017) - Coiras, Mayte; Ambrosioni, Juan; Cervantes, Francisco; Miró, José M.; Alcamí, José
ABSTRACT: Introduction : Infection caused by HIV-1 is nowadays a chronic disease due to a highly efficient antiretroviral treatment that is nevertheless, unable to eliminate the virus from the organism. New strategies are necessary in order to impede the formation of the viral reservoirs, responsible for the failure of the antiretroviral treatment to cure the infection. Areas covered : The purpose of this review is to discuss the possibility of using tyrosine kinase inhibitors (TKIs) for the treatment of HIV-1 infection. These inhibitors are successfully used in patients with distinct cancers such as chronic myeloid leukemia. The most relevant papers have been selected and commented. Expert opinion : The family of TKIs are directed against the activation of tyrosine kinases from the Src family. Some of these kinases are essential for the activation of CD4 + T cells, the major target of HIV-1. During acute or primary infection the CD4 + T cells are massively activated, which is mostly responsible for the generation of the reservoirs, the spread of the infection and the destruction of activated CD4 + T cells, infected or not. Consequently, we discuss the possibility of using TKIs as adjuvant of the antiretroviral treatment against HIV-1 infection mostly, but not exclusively, during the acute/recent phase.